The nature and origin of language - Bouchard, Denis (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; The emergence of language -- What is language that it could have evolved? -- The origin of language: from neurons to signs -- Explaining the properties of language